2018
DOI: 10.2174/1574891x13666180911095440
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Based Therapy for Treatment of Skin Cancer

Abstract: We focus especially on the topical lipid formulation approaches combined with chemotherapy, a field which specialises in target specificity, drug release control, and real time monitoring with the goal being to diminish unwanted side effects and their severity, achieving a cheaper treatment and a generally more efficient chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Essentially, this treatment would be localized to the interest of region, hopefully leaving surrounding normal tissue unaffected [115]. Lidocaine already comes in a topical/cream form, and topical chemotherapies are being investigated as new routes of treatment [116118]. In some cases of oral and oropharynx SCC, we found that T2R14 expression is upregulated, indicating the potential of developing targeted therapies, on a case-by-case basis for this receptor [45].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, this treatment would be localized to the interest of region, hopefully leaving surrounding normal tissue unaffected [115]. Lidocaine already comes in a topical/cream form, and topical chemotherapies are being investigated as new routes of treatment [116118]. In some cases of oral and oropharynx SCC, we found that T2R14 expression is upregulated, indicating the potential of developing targeted therapies, on a case-by-case basis for this receptor [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, invention or discovery of novel therapy based on nanotechnology as the alternative is urgent . Given several existing review articles describing nanoformulations for skin cancer therapy, we herein included only a brief discussion to make the article whole. , Niu et al designed a peptide-conjugated cationic AuNP (AuPT) loaded pDNAs system (AuPT/Mi221) to inhibit the encoding of miRNA-221. As an efficient carrier of pDNAs, AuPT improved the transfection efficiency and reversed the progression of melanoma .…”
Section: Np-based Formulation For Skin Disordersmentioning
confidence: 99%
“…Both lipophilic and hydrophilic drug molecules can be entrapped into liposomes in the lipid bilayer membrane, depending upon the categorized layer for therapeutics. Lipid soluble drugs get entrapped within the bi-layered lipidic membrane, while hydrophilic drugs get entrapped in the central aqueous core of the vesicles [57,58]. Liposomes are a potential carrier for controlled drug release of tumors therapeutic agents, antibiotics, for gene and antisense therapy through nucleic acid sequence delivery.…”
Section: Liposomesmentioning
confidence: 99%